92 The impact of a nurse-led heart failure service on complex device need. (May 2019) - Graby, John; Tibbs, Gemma; Giblett, Dawn; Dayer, Mark; Gosling, Oliver
Abstract : Introduction: The prevalence of left ventricular systolic dysfunction (LVSD) continues to rise. It is recognised that optimal medical therapy can improve ejection fraction (EF) in a proportion of patients. A nurse-led Heart Failure Service (HFS) was established in a district general hospital to deliver this, and previous analysis has demonstrated its efficacy in optimising HF drugs to recognised therapeutic doses. Complex devices (Implantable Cardiac Defibrillators [ICDs] or Cardiac Re-synchronisation Therapy Devices [CRTs]) are established treatments for HF patients if on Optimal Medical Therapy (OMT). The European Society of Cardiology (ESC) and National Institute for Clinical Excellence (NICE) guidelines have expanded their role with a broad cohort of patients eligible for this therapy. Aim: We sought to determine how many patients, who at baseline had an indication for device therapy, improved after OMT to an extent that they no longer had an indication for device therapy. Methods: A retrospective analysis was undertaken of the HFS database over a 5 year period recording ECG for QRS duration & morphology, surveillance of EF, device outcome. Exclusion criteria: baseline EF >35%; device in-situ or listed for prior to HFS referral; no identifiable baseline EF or ECG. Results: 502 patients were analysed and 264 patients met criteria for a new device or upgrade at baseline – 191 male (72%), 73 female (28%), median age 73 (IQR 64 – 80). 76/97 (78%) of potential CRT candidates (Pacing or Defibrillator component) were male. 16/97 (16%) improved to an EF >35% (median age 68 [IQR 64–72], 14 male [88%], 2 female [12%]). 4/16 (25%) of these patients underwent pharmacological or electrical cardioversion, which can contribute to EF improvement. There were 167 potential ICD candidates (115 male [69%]). 53/167 (32%) improved to an EF >35% (median age 68 [IQR 56–75], 33 male [61%]). 7/53 (13%) of these patients had other treatments that can also improve EF (cardioversion, 4; re-vascularisation, 2; valvuloplasty, 1). 69/264 (26.1%) patients did not require a device after optimal therapy had been delivered. Conclusion: We have demonstrated that in a significant proportion of HFS patients, the delivery of high quality OMT translates into an improvement in EF. Not all patients that strictly 'meet guideline criteria' will be offered a device, nor will all patients take up offer of a device. However, this improvement in EF is likely to benefit the patient symptomatically and prognostically, and carry a significant cost saving to healthcare institutions. A cost analysis study will be undertaken to further assess this. Conflict of Interest: Nil